2020
DOI: 10.1002/anie.202007270
|View full text |Cite
|
Sign up to set email alerts
|

Designable Aluminum Molecular Rings: Ring Expansion and Ligand Functionalization

Abstract: Presented herein are the AlIII molecular ring architectures from 8‐ring to 16‐ring. Although there are numerous reported cyclic coordination compounds based on transition metals, gallium, or lanthanides, the Al versions are less developed due to the fast hydrolysis nature of Al3+ ion. With the assistant of monohydric alcohols, a series of atomic precisely Al molecular rings based on benzoates are synthesized. The ring expansion of these Al‐rings from 8‐ring to 16‐ring is related to the monohydric alcohol struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 65 publications
2
69
0
Order By: Relevance
“…Hence, a similar synthetic method can be adopted for the construction of AlOCs [11] . Very recently, a series of aluminum molecular rings were synthesized by using CDH strategy [12] . In this work, a typical synthesis of the Al 32 clusters involves mainly three‐component solvothermal reactions with high phase purity under the optimized reaction conditions (Supporting Information, Figures S1–S8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a similar synthetic method can be adopted for the construction of AlOCs [11] . Very recently, a series of aluminum molecular rings were synthesized by using CDH strategy [12] . In this work, a typical synthesis of the Al 32 clusters involves mainly three‐component solvothermal reactions with high phase purity under the optimized reaction conditions (Supporting Information, Figures S1–S8).…”
Section: Resultsmentioning
confidence: 99%
“…[11] Very recently,aseries of aluminum molecular rings were synthesized by using CDH strategy. [12] In this work, at ypical synthesis of the Al 32 clusters involves mainly three-component solvothermal reactions with high phase purity under the optimized reaction conditions (Supporting Information, Figures S1-S8). Their structural components were confirmed by energy dispersive X-ray analysis (Figures S9-S15) and infrared spectroscopy (Figures S16-S22).…”
Section: Resultsmentioning
confidence: 99%
“…Coordination-Driven Self-Assembly of Heterometallic Frameworks Thec olorless crystals of Al 10 (INA) 10 (OEt) 20 (Al 10 ) (INA = isonicotinate, AlOC-79,F igure 2a)r ings were isolated according to our general synthesis of aluminum molecular rings (Figure 2b and S1). [21] Initial management of obtaining such aluminum molecular rings with extra coordination anchors encouraged us to explore their further assembly behavior. When adding cuprous thiocyanate in the reaction system of AlOC-79,yellow crystals of AlOC-80 were isolated (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Thea ssembly strategy is applicable and attempts to construct architectures based on different ring sizes were successful (Figure S8). In the course of further assembly,t he variety of copper salts and the presence of methylamine ethanol solutions play an important role.When cupric nitrate trihydrate is employed and the dosage of the methylamine ethanol solution is increased from 40 mLi nAlOC-82 to 120 mL, architecture is the presence of mesoporous rdo cages.T he rhombic dodecahedron cage is composed of six chargeneutral Al 8 (IN) 12 (OH) 4 (OPr n ) 8 (Al 8 ,i sostructural to the reported discrete ring, [21] S12). Bond valence sum (BVS) analysis (Table S1) combined with the XPS results (Figure S13) showed that the valence state of Cu centers with tetrahedral and planar Cu geometry was + 1and + 2, respectively.Asaresult, the whole architecture of Al 3f).…”
Section: Feasibility Of the Coordination-driven Self-assembly Strategymentioning
confidence: 99%
“…Some neutral Ti IV and Zr IV ‐based oxo‐clusters with the general formula M x O y (OH) z (RCOO) n (M=Ti IV , Zr IV ) are known, wherein the metal‐oxo/hydroxo clusters are capped by monoanionic, bidentate carboxylate groups [3a–e] . Very recently, neutral Al III ‐oxo clusters have been reported with the general formula Al(OH) x (OR) y (R′OOCPh) 3− x − y [3f] . A similar strategy was employed recently to isolate a neutral Ru III ‐based oxo‐cluster [21] .…”
Section: Introductionmentioning
confidence: 99%